2009
DOI: 10.1128/jb.00426-09
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characterization and Lytic Activities of Streptococcus agalactiae Bacteriophages and Determination of Lysogenic-Strain Features

Abstract: The application of mitomycin C induction to 114 genetically diverse Streptococcus agalactiae strains generated 36 phage suspensions. On electron microscopy of the phage suspensions, it was possible to assign the phages to the Siphoviridae family, with three different morphotypes (A, B, and C). Phage genetic diversity was evaluated by a PCR-based multilocus typing method targeting key modules located in the packaging, structural, host lysis, lysogeny, replication, and transcriptional regulation clusters and in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
40
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 49 publications
(61 reference statements)
0
40
0
Order By: Relevance
“…We previously identified and characterized bacteriophages and prophage remnants from S. agalactiae strain genomes and designed primer pairs recognizing the prophage sequences of S. agalactiae bacteriophages for use in PCR (12,47). Ten of these primer pairs were used here for the evaluation, by PCR, of the prophage content of S. agalactiae strains ( Table 1).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…We previously identified and characterized bacteriophages and prophage remnants from S. agalactiae strain genomes and designed primer pairs recognizing the prophage sequences of S. agalactiae bacteriophages for use in PCR (12,47). Ten of these primer pairs were used here for the evaluation, by PCR, of the prophage content of S. agalactiae strains ( Table 1).…”
Section: Methodsmentioning
confidence: 99%
“…They were first isolated in 1969 (39), and more-recent analyses of sequenced S. agalactiae strains have revealed the presence of abundant regions resembling prophages (16,44,45). We recently induced phages from S. agalactiae strains of various phylogenetic lineages, characterized them molecularly, and determined their lytic activities (12). The various molecular phage groups were found to correspond to particular strain lineages, with specific morphological features and lytic activities, suggesting a role for phage-mediated horizontal gene transfer in the evolution of the species and the emergence of lineages with a more specific role in particular diseases.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, LGT via ICE may also occur between S. agalactiae and other Streptococcus species (Davies et al, 2005, 2009; Haenni et al, 2010). Additional mobile genetic elements (MGE) such as phages have also been implicated in LGT within and among various Streptococcus species (Beres and Musser, 2007; Domelier et al, 2009; Ferretti et al, 2001; Holden et al, 2004; Salloum et al, 2010). …”
Section: Introductionmentioning
confidence: 99%
“…Most of strain-specific genes of S. agalactiae cluster in chromosomal genomic islands (Glaser et al 2002;Tettelin et al 2005). Several chromosomal prophages have been detected in this species, but they are less abundant in S. agalactiae than in S. pyogenes (Canchaya et al 2003;Domelier et al 2009). In addition, a first analysis carried out on the genome of eight human S. agalactiae strains indicated that a large part of the chromosomal genomic islands could be transferable by conjugation (Brochet et al 2008).…”
Section: Introductionmentioning
confidence: 91%